Two new earthworm species of the genus Amynthas Kinberg, 1867 (Annelida, Oligochaeta, Megascolecidae) from the Southeast region, Vietnam - Lam, Dang Hai; Tran, Anh-Thu T.; Nguyen, Anh D. (Zootaxa, 2024)
Two new earthworm species, namely Amynthas rarus sp. nov. and Amynthas tayninhensis sp. nov., are described from Tay Ninh Province, southeastern Vietnam. Amynthas rarus sp. nov. is recognized by having male pores in xix, two pairs of spermathecal pores in 6/7/8, and genital markings paired in vii, viii, 18/19, and 19/20. Amynthas tayninhensis sp. nov. is distinguished by having a pair of spermathecal pores in 5/6, numerous genital markings in transverse lines in 17/18 including three surrounding male pores, and spermatheca with fully developed diverticula. The COI fragments are also provided for those two new species.